2015
DOI: 10.1111/gtc.12305
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of MeCP2 attenuates circadian rhythm in CRISPR/Cas9‐based Rett syndrome model mouse

Abstract: Methyl-CpG-binding protein 2 (Mecp2) is an X-linked gene encoding a methylated DNA-binding nuclear protein which regulates transcriptional activity. The mutation of MECP2 in humans is associated with Rett syndrome (RTT), a neurodevelopmental disorder. Patients with RTT frequently show abnormal sleep patterns and sleep-associated problems, in addition to autistic symptoms, raising the possibility of circadian clock dysfunction in RTT. In this study, we investigated circadian clock function in Mecp2-deficient mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…We have shown that approximately threefold numbers of oocytes could be collected from C57BL/6 female mice at 4 weeks of age by the administration of IASe compared with the conventional administration of IAS or eCG alone. We and other investigators have confirmed that fertilized oocytes created by IVF via the conventional superovulation method were applicable for creating genome-edited mice (Nakagawa et al, 2014, 2015; Li et al, 2014; Miura et al, 2015; Tsuchiya et al, 2015; Kaneko and Mashimo, 2015; Nakao et al, 2016; Sakurai et al, 2016). However, it has not yet been elucidated whether the ultra-superovulation technique can be applied for the generation of genome-edited mice.…”
Section: Introductionmentioning
confidence: 58%
“…We have shown that approximately threefold numbers of oocytes could be collected from C57BL/6 female mice at 4 weeks of age by the administration of IASe compared with the conventional administration of IAS or eCG alone. We and other investigators have confirmed that fertilized oocytes created by IVF via the conventional superovulation method were applicable for creating genome-edited mice (Nakagawa et al, 2014, 2015; Li et al, 2014; Miura et al, 2015; Tsuchiya et al, 2015; Kaneko and Mashimo, 2015; Nakao et al, 2016; Sakurai et al, 2016). However, it has not yet been elucidated whether the ultra-superovulation technique can be applied for the generation of genome-edited mice.…”
Section: Introductionmentioning
confidence: 58%
“…However, this was not statistically significant ( P =0.6). The 18 previously published studies studies that have targeted individual loci in the mouse genome with single sgRNAs have not specifically addressed the symmetry of deletions101117183132333435363738394041424344. Deleted sequences were available from seven studies11183134394344 (Supplementary Data 1), but only one18 showed large enough data sets to permit a direct comparison with ours.…”
Section: Resultsmentioning
confidence: 99%
“…The C57BL/6 strain has been widely used as a genetic background for congenic and mutant mice because genome mapping has been done [4]. Recently, this strain is often used for gene manipulation using clustered, regularly interspaced short palindromic repeat/CRISPR-associated (CRISPR/Cas) and transcription activator-like effector nucleases (TALEN) [43][44][45]. For these reasons, our new FSGS model mice may be useful in renal studies using genetic manipulation and help uncover the molecular mechanisms behind podocytopathy.…”
Section: Discussionmentioning
confidence: 99%